Comparative study of different subgrid-scale models for large eddy simulations of magnetohydrodynamic turbulent duct flow in OpenFOAM. (18th July 2017) - Mao, Jie; Zhang, Kunlei; Liu, Ke
Highlights: Three different subgrid models for LES are compared in MHD turbulent flow modeling. The dynamic Smagorinsky model is suitable for simulating the MHD turbulent flow. The suppressing effect of the applied magnetic field on MHD flow is anisotropic. The dynamic Smagorinsky model can predict the laminar-turbulent transition precisely. Abstract: Magnetohydrodynamic (MHD) turbulent duct flow has been numerically investigated using large eddy simulation (LES) method with different subgrid-scale models in OpenFOAM environment. Smagorinsky, dynamic Smagorinsky, and dynamic one equation eddy viscosity subgrid-scale models have been used to simulate MHD square duct flow with R e = 5681 . The results demonstrate that the average velocity and the turbulent kinetic energy obtained from the dynamic Smagorinsky subgrid-scale model agree well with those from direct numerical simulations (DNS). Furthermore, a MHD duct flow with R e = 29000 has been modeled using dynamic Smagorinsky subgrid-scale model. The results are compared with the results of coherent structure model. A good agreement in mean velocity values is observed. The agreement confirms that the dynamic Smagorinsky subgrid-scale model suitable for modeling MHD turbulent duct flows. Finally, LES with dynamic Smagorinsky subgrid-scale model has been used to simulate MHD flow in a square duct with electrically insulated walls with the same Reynolds number and different Hartmann number. The results for the mean velocity, velocity fluctuations and skin friction coefficient are presented. The laminar-turbulent transition parameters agree with the value given by Chaudhary's DNS results.